Tool Support for Traceability of Software Artefacts - Kamalabalan, K.; Uruththirakodeeswaran, T.; Thiyagalingam, G.; Wijesinghe, D.B.; Perera, I.; Meedeniya, D. (IEEE, 2015)
Artefact management in a software development process is a challenging problem. Often there is a wide variety of artefacts, which are maintained separately within a software development process, such as requirement specifications, architectural concerns, design specifications, source codes and test cases, which are essential to software engineering. Artefact inconsistency is a major problem since these artefacts evolve at different rates. Maintaining traceability links among these artefacts and updating those artefacts accordingly can be a solution to address artefact inconsistency. There is a need for establishing these artefact traceability links in semi-automatic way. Proper management and visualization tool is required for effective software artefact management in an incremental software development. We present a prototype tool to establish artefact traceability links and visualization of those. This paper describes the research methodology and relevant research carried out for semi-automatic traceability link establishment and visualization of software artefacts.
Keywords: Artefacts; Traceability Links; Artefact Traceability Visualization;\; Artefacts Consistency Management